Frazer-Imregh Monika, Életmód, asztrológia, mágia a reneszánszban, Budapest, L’Harmattan, 2023. - Hamvas, Endre Ádám (Antikvitás & Reneszánsz, 2023)
Frazer-Imregh Monika, Életmód, asztrológia, mágia a reneszánszban, Budapest, L’Harmattan, 2023.